Visual performance in preterm infants with brain injuries compared with low-risk preterm infants - Leonhardt, Merçè; Forns, Maria; Calderón, Caterina; Reinoso, Marta; Gargallo, Estrella (Early human development, 2012)
Neonatal brain injuries are the main cause of visual deficit produced by damage to posterior visual pathways. While there are several studies of visual function in low-risk preterm infants or older children with brain injuries, research in children of early age is lacking. To assess several aspects of visual function in preterm infants with brain injuries and to compare them with another group of low-risk preterm infants of the same age. Forty-eight preterm infants with brain injuries and 56 low-risk preterm infants. The ML Leonhardt Battery of Optotypes was used to assess visual functions. This test was previously validated at a post-menstrual age of 40weeks in newborns and at 30-plus weeks in preterm infants. The group of preterm infants with brain lesions showed a delayed pattern of visual functions in alertness, fixation, visual attention and tracking behavior compared to infants in the healthy preterm group. The differences between both groups, in the visual behaviors analyzed were around 30%. These visual functions could be identified from the first weeks of life. Our results confirm the importance of using a straightforward screening test with preterm infants in order to assess altered visual function, especially in infants with brain injuries. The findings also highlight the need to provide visual stimulation very early on in life.